Granada Relocation Center. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Panorama of Granada Relocation Center, Amache, Colorado showing in the foreground a typical barracks unit consisting of 12 six-room apartment barrack buildings, a recreation hall, mess hall, laundry and bathhouse.